Pengaruh Sukuk Dana Haji, Inflasi dan Nilai Tukar Rupiah Terhadap Kinerja Keuangan Perbankan Syariah Periode 2010-2015 - Rif’ah, Sifwatir (Al-Musthofa: Journal of Sharia Economics, 2018)
It’s a synchronic analysis based on the data 2010-15. The purpose of this study is to analyze the influence of Indonesia hajj sukuk funds (Sukuk dana haji Indonesia -SDHI- or syariah obligation), Inflation, rupiah exchange rate, and third party funds toward Islamic banking financial performance in Indonesia for the period 2010 to 2015 which is proxied by return on assets (ROA) partially and simultaneously. The method applied in this research is multiple regressions linear. The research using secondary data based on 5 years finance report by purposive sampling and obtained six Islamic bank which meet the criteria, those are Bank Muamalat Indonesia, Bank Syariah Mandiri, BRISyariah, Bank Mega Syariah, Bank Syariah Bukopin, and BCA Syariah. This study uses pooled ordinary least square (POLS) or panel data of eviews 7 as a tool analysis. The results show that are simultaneous influence of variable sukuk hajj funds, inflation, rupiah exchange rate, and third party fund toward return on assets of Islamic banking. The result also show there is a significant partially influence that rupiah exchange rate has a negative effect and significant toward return on assets of Islamic banking. Third party funds has a positive effect and significant on return on assets of Islamic banking. Whereas Indonesia hajj sukuk funds and inflation have no significant effect toward return on assets of Islamic banking. Indonesia hajj Sukuk fundsis expected to help the liquid of Islamic banking as well, so it can improve the function of the bank intermediary to the public perfectly.